KONSEP KETUHANAN MENURUT PRESPEKTIF SAMKYA DARSANA - Astu Arya Putra; Kadek Yuli Wahyu Astini (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
Philosophy is a rational aspect of religion and is an integral part of religion. Hinduism has a view called Darsana. Darśana is a part of Hindu writing which requires sharpness of intelligence, reasoning, and feeling, because the main problem discussed is the essence of the whole Vedic understanding in philosophy. The Hindu philosophy has a very noble, noble, unique and systematic value. Where Hindu philosophy has six views called Sad Darsana. In general, every Sad Darsana discusses the main teachings of Hinduism starting from the concept of God, cosmology, soul / spirit and so forth. In this article we will discuss the concept of God from the perspective of Samkhya Darsana. Samkhya Darsana is one part of the Sad Darsana. Seeking knowledge through true Samkhya Darsana, in the Samkhya philosophy outlines three methods, namely: Pratyaksa pramana or direct observation; Anumana pramana (inference); Apta Vakya. Therefore, in the concept of God, Samkhya believes in two elements namely Purusa and Prakerti, both elements are believed to be the origin of the creation of the universe and its contents.